EFFICIENCY OF TEACHING MATHEMATICS WITH USING COMPUTER - MAROŠ, Milan; KOPRDA, Štefan; BREČKA, Peter (Trends in education, 2009)
In this work we deal with computer, their usage in mathematics and influence on the efficiency of teaching. In the practical part of this work we deal with educational software intended for the section of a cube. Using this software was the main theme of our research work. We realized the research with two groups of students, the experimental and the control one. Within the evaluation of research we use the test results and the elaborated questionnaires of both groups.
Keywords: Efficiency of education; Mathematics education; Didactic means; Computer-based training; Educational software; E-learning; Electronic schoolbook.